2008
DOI: 10.1111/j.1365-2125.2008.03266.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of flucloxacillin tubular renal secretion by piperacillin

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Most β‐lactams are excreted by filtration and to a greater extent by tubular secretion, which is a capacity‐limited saturable pathway. • Pharmacokinetic interactions between co‐administered β‐lactams have been frequently reported; however, their mechanism and possible clinical benefits are not well defined. • We are not aware of the interaction between piperacillin and flucloxacillin being reported in the literature. WHAT THIS STUDY ADDS • Piperacillin inhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…The LLOQs are sufficiently lower than expected trough concentration or real plasma levels [61][62][63][64][65][66] and therefore the method can accurately determination concentrations in the expected low ranges. Concentrations above the upper limit of quantification can be diluted with blank drug free plasma as needed to put the concentration in the range of the calibration curve.…”
Section: Calibration Curve and Limit Of Quantificationmentioning
confidence: 99%
“…The LLOQs are sufficiently lower than expected trough concentration or real plasma levels [61][62][63][64][65][66] and therefore the method can accurately determination concentrations in the expected low ranges. Concentrations above the upper limit of quantification can be diluted with blank drug free plasma as needed to put the concentration in the range of the calibration curve.…”
Section: Calibration Curve and Limit Of Quantificationmentioning
confidence: 99%
“…Model R2 represents a more physiological model of the kidney with renal blood flow, glomerular filtration from the kidney compartment, proximal and distal tubule compartments, and a urine compartment (17). Model S1 is a one-compartment model with linear and saturable clearance processes described by glomerular filtration and active tubular secretion, as well as linear nonrenal clearance (18). Model S2 is a mechanistic semiphysiological model, incorporating renal blood flow from the central compartment to the kidneys.…”
Section: Structural Modelsmentioning
confidence: 99%
“…1) were selected for analysis based on the available models within the literature (16)(17)(18)(19). The differential equations for the structural models are listed in the supplemental data.…”
Section: Structural Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Furthermore, PIPC inhibits OATs. Landersdorfer et al 19) has found that when 3.0 g of PIPC was administered alone, PIPC clearance was smaller than when 1.5 g of PIPC was administered.…”
mentioning
confidence: 99%